2010
DOI: 10.1158/0008-5472.can-09-3109
|View full text |Cite
|
Sign up to set email alerts
|

CD73 on Tumor Cells Impairs Antitumor T-Cell Responses: A Novel Mechanism of Tumor-Induced Immune Suppression

Abstract: CD73, originally defined as a lymphocyte differentiation antigen, is thought to function as a cosignaling molecule on T lymphocytes and an adhesion molecule that is required for lymphocyte binding to endothelium. We show here that CD73 is widely expressed on many tumor cell lines and is upregulated in cancerous tissues. Because the ecto-5′-nucleotidase activity of CD73 catalyzes AMP breakdown to immunosuppressive adenosine, we hypothesized that CD73-generated adenosine prevents tumor destruction by inhibiting … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
384
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 374 publications
(410 citation statements)
references
References 51 publications
21
384
2
3
Order By: Relevance
“…Ecto-5′-NT/CD73 expression in cancer cells has been also linked with drug resistance [26,59] and immune escape [44,60]. Moreover, researchers have already targeted ecto-5′-NT/ CD73 in an attempt to develop promising therapies, for instance, ecto-5′-NT/CD73 inhibitors have shown antiproliferative effects in bladder cancer cell lines and gliomas [61,62], and decrease in ovarian cancer progression [63]. The treatment of mice with anti-CD73 antibody inhibited breast tumor growth and metastasis [20], and the use of RNA interference of ecto-5′-NT/CD73 inhibited cell growth and invasion in human breast cancer cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…Ecto-5′-NT/CD73 expression in cancer cells has been also linked with drug resistance [26,59] and immune escape [44,60]. Moreover, researchers have already targeted ecto-5′-NT/ CD73 in an attempt to develop promising therapies, for instance, ecto-5′-NT/CD73 inhibitors have shown antiproliferative effects in bladder cancer cell lines and gliomas [61,62], and decrease in ovarian cancer progression [63]. The treatment of mice with anti-CD73 antibody inhibited breast tumor growth and metastasis [20], and the use of RNA interference of ecto-5′-NT/CD73 inhibited cell growth and invasion in human breast cancer cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular adenosine generated by CD73 on tumor cells negatively regulated both activation and effector phases of the antitumor T-cell response. However, it promoted T-cell apoptosis by binding A2aAR on T cells (27). Stagg et al reported that CD73-derived adenosine enhanced tumor-cell migration in vitro and metastasis in vivo through the activation of A2bAR.…”
Section: Discussionmentioning
confidence: 99%
“…in [201,202]). The enzyme has a broad tissue distribution, and it is expressed by subpopulations of human T and B lymphocytes and also by a considerable variety of tumor cells [203]. Catalytic activity varies considerably between individual tissues [204].…”
Section: Ecto-5′-nucleotidasementioning
confidence: 99%